Liquid chromatography coupled to molecular fluorescence with postcolumn UV sensitization for thimerosal and derivative compounds monitoring in environmental samples - Acosta, Maria Gimena (2016)
A HPLC coupled with molecular fluorescence (MF) spectrometry method for determination of thimerosal (THM, sodium ethylmercurythiosalicylate, C9H9HgNaO2S), and derivatives is proposed. A sensitization of MF was provoked by UV irradiation of analytes in a home-made photoreactor that served as interface between the LC column and MF spectrometer. This method is applied to determination of THM, ethyl mercury, and thiosalicylic acid in samples of pharmaceutical industry effluents, and waters of La Carolina and Jáchal rivers situated in the center-west side of San Luis city and in the east of San Juan city (Middle West, Argentine) where the effluents are dumped. The LODs calculated on basis of 3σ criterion were 1.8, 5, and 0.05 μmol/L for THM, ethyl mercury, and for thiosalicylic acid, respectively.